Exploiting Fine-Grained Spatial Optimization for Hybrid File System Space - No, Jaechun; Park, Sung-Soon; Lim, Cheol-Su (Computing and Informatics, 2017)
Over decades, I/O optimizations implemented in legacy file systems have been concentrated on reducing HDD disk overhead, such as seek time. As SSD (Solid-State Device) is becoming the main storage medium in I/O storage subsystems, file systems integrated with SSD should take a different approach in designing I/O optimizations. This is because SSD deploys the peculiar device characteristics that do not take place in HDD, such as erasure overhead on flash blocks and absence of seek time to positioning data. In this paper, we present HP-hybrid (High Performance-hybrid) file system that provides a single hybrid file system space, by combining HDD and SSD partitions. HP-hybrid targets for optimizing I/O while considering the strength and weakness of two different partitions, to store large-scale amounts of data in a cost-effective way. Especially, HP-hybrid proposes spatial optimizations that are executed in a hierarchical, fine-grained I/O unit, to address the limited SSD storage resources. We conducted several performance experiments to verify the effectiveness of HP-hybrid while comparing to ext2, ext4 and xfs mounted on both SSD and HDD.